1997
DOI: 10.1007/bf03348005
|View full text |Cite
|
Sign up to set email alerts
|

Fine-needle aspiration biopsy of thyroid nodules: Impact on clinical practice

Abstract: retrospective the 1st period and prospective the 2nd and 3rd periods. During the 1st and 2nd periods, decision for surgery was based on clinical parameters together with results of 99Tc radionucleotide scan and B mode ultrasound studies. In the 3rd period surgical decision was based principally on cytologic results. We comparatively studied the frequency of surgical operation and frequency of malignancy in surgical thyroid specimens between the study periods. Determination of sensitivity, specificity and accur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0
6

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 33 publications
0
13
0
6
Order By: Relevance
“…In conclusion, US-FNAB improves the quality of diagnosis in the preoperative assessment of thyroid nodules to select patients for surgery [10,12,14,20,27] even in an endemic goitre area. Thus, intra-operative procedures can be planned in advance in cases with malignant cytology, or intra-operative frozen sections may be included in cases with suspicious cytological results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In conclusion, US-FNAB improves the quality of diagnosis in the preoperative assessment of thyroid nodules to select patients for surgery [10,12,14,20,27] even in an endemic goitre area. Thus, intra-operative procedures can be planned in advance in cases with malignant cytology, or intra-operative frozen sections may be included in cases with suspicious cytological results.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the best method for a preoperative diagnostic evaluation is fine-needle aspiration biopsy (FNAB) [1,5,[9][10][11]. This method allows patients to be detected with suspicious and malignant nodules, who need to have surgery, out of the great number of patients with thyroid nodules [6,8,9,12]. The efficacy of this diagnostic approach is already well established [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Since then, several studies have reported that USG-FNAC reduces the inadequacy rate of conventional FNAC. 7,8,9,10 It also has the major advantage of real time monitoring which help in accurate localisation of needle tip during aspiration. 5 There are only two recent guidelines available on the practice of USG-FNAC; both were published in 2006.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison with other European countries, our ASR in the final period of time, 1994-2001, (8.2 per 100,000-year in women and 2.65 in men) is similar to the reports from our neighbouring countries such as Portugal, France and Italy and is higher than that reported by the IARC for Spain (period 1997-1999) (Ferlay et al, 2004). A previous study in our community (Garcia-Mayor et al, 1997), reported a decrease in the number of patients requiring surgical treatment with an increase in the frequency of malignancy in the surgical specimens after the introduction of FNAB in the management of nodular thyroid disease in 1991. However, when we studied the total number of thyroid surgeries performed in our population, we found that the rate of population undergoing thyroid surgery significatively increased over time with an increase in the ratio of total thyroidectomy for other kind of thyroidectomy.…”
Section: Discussionmentioning
confidence: 82%